Graduating students 2000. - Nilsson, Lars (Malmö : Malmö Art Academy, 2000)
Adelman, Mats ; Dahlberg, Jonas ; Ekman, Anna ; Eriksson, Malin ; Forfang, Katrine ; Friberg, Ylva ; Joannides, Gabriella ; Johansson, Liselott ; Kopp, Viktor ; Ravn, Kine ; Sarén, Lena ; Sköld, Nils Magnus ; Svensson, David ; Svensson, Johan ; Winmalm, Nichlas
Engels
boek
Keywords: Zweden; Malmö